2021
DOI: 10.1136/jitc-2020-002181
|View full text |Cite
|
Sign up to set email alerts
|

Deep immune profiling reveals targetable mechanisms of immune evasion in immune checkpoint inhibitor-refractory glioblastoma

Abstract: BackgroundGlioblastoma (GBM) is refractory to immune checkpoint inhibitor (ICI) therapy. We sought to determine to what extent this immune evasion is due to intrinsic properties of the tumor cells versus the specialized immune context of the brain, and if it can be reversed.MethodsWe used CyTOF mass cytometry to compare the tumor immune microenvironments (TIME) of human tumors that are generally ICI-refractory (GBM and sarcoma) or ICI-responsive (renal cell carcinoma), as well as mouse models of GBM that are I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 48 publications
2
48
1
Order By: Relevance
“…To verify the immune competence of these mouse models, we first characterized the TIME of the primary IUE tumors by performing CyTOF mass cytometry on extracted whole tumor tissue, as described previously. 30 Analysis of gated immune cell populations demonstrated that both histone wildtype and mutant IUE tumors consisted predominantly of myeloid cells, specifically microglia and macrophages, and very few lymphocytes, corresponding to what has previously been observed in human DMG autopsy tissue ( Figure 3 , Supplementary Figure S7 ). 12 , 13 We subsequently analyzed the TIME in our secondary allograft models by staining for these immune cell populations by IHC and IF and comparing these to analogous human DMG tissues.…”
Section: Resultssupporting
confidence: 75%
“…To verify the immune competence of these mouse models, we first characterized the TIME of the primary IUE tumors by performing CyTOF mass cytometry on extracted whole tumor tissue, as described previously. 30 Analysis of gated immune cell populations demonstrated that both histone wildtype and mutant IUE tumors consisted predominantly of myeloid cells, specifically microglia and macrophages, and very few lymphocytes, corresponding to what has previously been observed in human DMG autopsy tissue ( Figure 3 , Supplementary Figure S7 ). 12 , 13 We subsequently analyzed the TIME in our secondary allograft models by staining for these immune cell populations by IHC and IF and comparing these to analogous human DMG tissues.…”
Section: Resultssupporting
confidence: 75%
“…With the advent of high-throughput multiplexed analytical technologies, peripheral blood is now suitable for deeper immune profiling. As peripheral blood sampling is readily available, minimally invasive, and repeatable, the use of blood-based immune biomarkers can compensate for the abovementioned limitations of tissue-based immune biomarkers during cancer immunotherapy [11,15,[18][19][20][21][22][23]. This review aimed to summarize pivotal findings related to blood-based immune biomarkers in patients with solid cancer treated with ICIs (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Gene set enrichment analysis and KEGG pathway analysis both confirmed that IFNγ response, antigen-processing and presentation machinery, along with multiple proinflammatory signatures, were significantly enriched after IDH1 R132H inhibition compared with the control ( figure 6B ). 21 As Pd-l1 is known to be upregulated in response to IFNγ signaling and PD-L1 + myeloid populations are enriched in gliomas, 22 we used FC to evaluate the in vivo protein expression of HLA-DR and PD-L1 on the surface of immune cells in the TME and observed that both molecules were significantly upregulated in response to AG-881 treatment ( figure 6C ).…”
Section: Resultsmentioning
confidence: 99%